Inflammatory response in the early prediction of severity in human acute pancreatitis. - Viedma, J A (1994)
The role of the inflammatory response in acute pancreatitis and its relation with the clinical course was examined. This study examined if the serial measurement of polymorphonuclear granulocyte (PMN) elastase/A1PI complex, phospholipase A catalytic activity, C reactive protein, and other acute phase proteins, and the protease inhibitor alpha 2-macroglobulin, provides meaningful information for prognosis. Eighty non-consecutive patients with acute pancreatitis, classified according to their clinical outcome into mild (n = 40) and severe pancreatitis (n = 40), were followed up daily. Between 48 hours, median values of PMN-elastase, C reactive protein--and most of the acute phase proteins--and phospholipase A activity, were significantly higher in the severe pancreatitis group. PMN elastase shows a dynamic course and it reaches an early peak value at days 1-2, followed by C reactive protein (days 2-4) phospholipase A (day 3), and a negative peak for alpha 2-macroglobulin (days 4-5). PMN elastase (day 1) and C reactive protein (day 2) were selected by discriminant analysis as the most useful variables studied to allow the early accurate prediction of severity (sensitivity 100%, specificity 95%). Little or no predictive additional value was found for all other variables studied. These results strongly suggest a close relation between inflammatory parameters and clinical course in acute pancreatitis, and discriminant analysis of these variables provides a useful method to classify severity.